Activities, Employment, and Wages in Rural and Semi-Urban Mexico - Verner, Dorte (World Bank, Washington, DC, 2012)
The author addresses the labor markets in rural and semi-urban Mexico. The empirical analyses show that non-farm income shares increase with overall consumption levels and, also, with time. Rural-dwellers in lower quintiles of the consumption distribution tend to earn a larger share of their nonagricultural incomes from wage labor activities. For the poorest, low-productivity wage labor activities are important. The quantile wage regression analysis for rural Mexico shows a rather heterogeneous impact pattern of individual characteristics across the wage distribution on monthly wages. The author's findings reveal that education is key to earning higher wages, and that workers in more dispersed rural areas earn less than their peers in semi-urban rural areas (localities with less than 15,000 inhabitants). The rural non-farm sector is heterogeneous and includes a great variety of activities and productivity levels across non-farm jobs. Moreover it can reduce poverty in a couple of distinct but qualitatively important ways in rural Mexico. The analysis of non-farm employment in rural Mexico suggests that the two key determinants of access to employment and productivity in non-farm activities are education and location.